Application of Fuzzy C-Means Algorithm in Clustering Levels of Weed Killer Toxic Use (Case Study: PT. Daria Dharma Pratama) - Felic Valentino; Herlina Latipa Sari; Rizka Tri Alinse (GATOTKACA Journal (Teknik Sipil, Informatika, Mesin dan Arsitektur), 2021)
PT. Daria Dharma Pratama is one of PT Kebun Sawit as well as the manufacture of CPO (Crude Palm Oil) in Mukomuko Regency. Weed weeds or herbicides are compounds or materials that are spread on agricultural land to suppress or eradicate plants that cause a decrease in yield (weeds). So far, the process of managing data on the use of weed killer poison at PT Daria Dharma Pratama is still using the manual method, namely by identifying the number of estates and the amount of use of weed killer poison every month then inputting the data into an office application package for making reports on the use of weed killer poison per estate. in 1 year. This research was conducted to determine the level of use of weed killer poison using the Fuzzy C-Means Algorithm and create an application that will apply the Fuzzy C-Means Algorithm for the clustering process. Application of Clustering the level of use of weed killer poison at PT. Daria Dharma Pratama can simplify the process of managing data on the amount of weed poison used in each estate and can make it easier for PT. in obtaining information on the level of use of weed killer poison which is grouped into high and low based on the results of the clustering that has been carried out using the Fuzzy C-Means Algorithm. Application of Clustering the level of use of weed killer poison at PT. Daria Dharma Pratama was created using the Visual Basic .Net programming language and SQL Server 2008 Database. Based on the grouping carried out using the data for the last 3 years (2018, 2019, 2020), it was found that the Number of Toxic Use Groups in Cluster I was 9 and the Number of Use Groups Toxins in Cluster II A total of 12. Based on the results of the tests that have been carried out, functionally from the Clustering Application the level of use of weed killer poisons at PT. Daria Dharma Pratama has worked as expected and is able to provide information on the level of use of gulam killer poison